AMBIVALENCE IN GENDER PORTRAYALS IN GOOSEBUMPS (2015) AND GOOSEBUMPS: HAUNTED HALLOWEEN (2018) - Kardono, Tyasyifa Wimahavinda; Hapsarani, Dhita (UI Scholars Hub, 2023)
The horror genre is notorious for sexist depictions of female heroines, which heavily imposes traditional gender stereotypes. This paper analyses Goosebumps (2015) and Goosebumps: Haunted Halloween (2018), which are the movie adaptations of R.L Stine’s horror book series. It aims to see the possibility of the female heroines and male heroes to defy conventional gender stereotypes and determine the female heroines’ agency as horror movies tend to objectify the female characters. This paper uses the Cult of True Womanhood (Welter, 1966), Male Gender Role Identity (Pleck, 1981) and representation theory (Hall, 1997) to analyse the dialogues and interaction of the characters, and the agencies of the female heroines in the two movies. This research shows the apparent ambivalence portrayals as the text often contradicts the characters’ depiction in the earlier part of the film and the ending. In the beginning of the movies, the female heroines are depicted as empowered and independent, but as the story progresses, they become characters that need male heroes’ help and support to overcome problems.